Synergistic effects of neuroprotective drugs with intravenous recombinant tissue plasminogen activator in acute ischemic stroke: A Bayesian network meta-analysis. - Chun Dang; Qinxuan Wang; Yijia Zhuang; Qian Li; Yaoheng Lu; Ying Xiong; Li Feng (PLoS ONE)
Neuroprotective drugs as adjunctive therapy for adults with acute ischemic stroke (AIS) remains contentious. This study summarizes the latest evidence regarding the benefits of neuroprotective agents combined with intravenous recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis. This study conducted a structured search of PubMed, the Cochrane Library, EMBASE, Wanfang Data, and CNKI databases from their inception to March 2024. Grey literature was also searched. The outcomes included efficacy (National Institutes of Health Stroke Scale (NIHSS) score and Barthel Index (BI) score) and safety (rate of adverse reactions). A total of 70 randomized controlled trials were selected for this network meta-analysis (NMA), encompassing 4,140 patients with AIS treated using different neuroprotective agents plus RT-PA, while 4,012 patients with AIS were in control groups. The top three treatments for NIHSS scores at the 2-week follow-up were Edaravone Dexborneo with 0.9 mg/kg rt-PA, Edaravone with 0.9 mg/kg rt-PA, and HUK with 0.9 mg/kg rt-PA. HUK with 0.9 mg/kg rt-PA, Dl-3n-butylphthalide with 0.9 mg/kg rt-PA, and Edaravone Dexborneo with 0.9 mg/kg rt-PA were ranked the top three for BI scores at the 2-week follow-up. The top three treatments with the lowest adverse effect rates were 0.6 mg/kg rt-PA, HUK with 0.9 mg/kg rt-PA, and Edaravone Dexborneo with 0.9 mg/kg rt-PA due to their excellent safety profiles. Compared to rt-PA alone, the combination treatments of Edaravone+rt-PA, Edaravone Dexborneol+rt-PA, HUK+rt-PA, Dl-3n-butylphthalide+rt-PA, and Ganglioside GM1+rt-PA have shown superior efficacy. This NMA suggest that combination therapies of neuroprotective agents and rt-PA can offer better outcomes for patients with AIS. The results support the potential integration of these combination therapies into standard AIS treatment, aiming for improved patient outcomes and personalized therapeutic approaches.